Penegakan Hukum Pelaku Tindak Pidana Artificial Intelegence (Deepfake) Dalam Perspkektif Hukum Positif Indonesia - Dimas Tri Wicaksono; Niken Putri Lestari; Friyandi Prasetya (LPPM UNIVERSITAS Pertiba Pangkalpinang, 2026)
The rapid advancement of artificial intelligence has significantly transformed various aspects of life and provided substantial benefits across multiple fields. However, the emergence of artificial intelligence has also generated negative impacts, particularly the rise of deepfakes, which are frequently exploited by cybercriminals to deceive victims for various purposes. This study examines law enforcement regulations applicable to deepfake-related crimes under Indonesian positive law, specifically the Criminal Code, the Personal Data Protection Law, the Electronic Information and Transactions Law, and the Sexual Violence Crime Law. This research employs a normative juridical method using statutory, conceptual, and case-based approaches. The findings show that several legal frameworks in Indonesia can be applied to deepfake crimes. The Criminal Code and the Electronic Information and Transactions Law are the legal instruments most commonly used in prosecuting deepfake offenders, and in several cases, verdicts have even become legally binding.